Spatial large-span structures - A. K. Yusupov; H. M. Muselemov; R. I. Vishtalov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. This article discusses spatial large-span structures; provides features of their work; as well as layout examples. General dimensions and ways of stabilizing displacements are given.Method. The features of the work and layout of spatial large-span structures; as well as calculation formulas are given. The types of sections and nodes of conjugation of elements are presented. A technique is described that allows stabilizing the movements of largespan pavements.Result. The given structural schemes; as well as the analysis of their work; allow designing large-span spatial systems in the form of convex and concave structures that have high reliability; minimal weight; and high manufacturability in manufacturing; transportation and installation.Conclusion. The proposed rational design solutions make it possible to reduce the own weight of spatial convex and concave coatings; which have the necessary rigidity; strength and stability. The types of structural schemes; sections and junctions of elements considered in the article are widely used in the practice of design and construction.